2013
DOI: 10.35536/lje.2013.v18.i2.a1
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Relationship between Inflation and Gold Prices: Evidence from Pakistan

Abstract: In this study, we formulate a new inflation equation to capture the potential effects of gold and stock prices on inflation in Pakistan. We aim to assess the inflation-hedging properties of gold compared to other assets such as real estate, stock exchange securities, and foreign currency holdings. Applying time-series econometric techniques (cointegration and vector error correction models) to data for 1960–2010, we find that gold is a potential determinant of inflation in Pakistan. On the other hand, it also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 56 publications
4
8
0
1
Order By: Relevance
“…For the United States, Jaffe () found that gold returns had no significant relationship with expected inflation over the 1971–1987 period and Blose () found no relationship between nominal gold returns and expected inflation from 1988 to 2008. Tufail and Batool () reported that gold returns provided a complete hedge against unexpected but not expected inflation. Similarly, Ghazali et al () uncovered no significant relationship between gold returns and inflation expectation in Malaysia.…”
Section: Introductionmentioning
confidence: 99%
“…For the United States, Jaffe () found that gold returns had no significant relationship with expected inflation over the 1971–1987 period and Blose () found no relationship between nominal gold returns and expected inflation from 1988 to 2008. Tufail and Batool () reported that gold returns provided a complete hedge against unexpected but not expected inflation. Similarly, Ghazali et al () uncovered no significant relationship between gold returns and inflation expectation in Malaysia.…”
Section: Introductionmentioning
confidence: 99%
“…That market has been steadily increasing for ten years. According to a World Bank estimate, the average size of a country's real estate assets constitutes between 60 and 70% of the country's total wealth; if these estimates are applied to Pakistan, the estimated size of the real estate sector would be $300 to $400 billion (Tufail & Batool, 2013). The transactions in the real estate market have been carried out by an increasing number of uneducated agents and dealers who do not have the necessary IT and finance related skills to serve their clientele.…”
Section: Market Competitiveness and Transaction Transparency In Pakistanmentioning
confidence: 99%
“…The increase in inflation shows an increase in the prices of goods in general, including rice and gold (Thufail & Batool, 2013). Gold is a determinant of the size of the zakat maal threshold, namely gold and silver zakat or currency zakat, trade zakat and money saving zakat.…”
Section: Based Onmentioning
confidence: 99%